Self-images contrast enhancement for displacement Talbot lithography by means of composite mesoscale amplitude-phase masks; Journal of Optics; Vol. 22, iss. 1 - Geints Yu. E. Yuri; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich; Zemlyanov Yu. E. Alexander (2020, 2020)
Title screen